2012
DOI: 10.1116/1.3684982
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrogen on the thermionic electron emission from nitrogen-incorporated polycrystalline diamond films

Abstract: Articles you may be interested inSubstrate-diamond interface considerations for enhanced thermionic electron emission from nitrogen doped diamond films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 13 publications
4
26
1
Order By: Relevance
“…This effect was illustrated in previous work by Paxton et al (2012a), which observed that exposure of diamond cathodes to a low-energy hydrogen plasma prior to testing resulted in drastically enhanced thermionic emission current relative to as-grown diamond films by four orders of magnitude. Thermionic emission can be described by the Richardson equation seen in Eq.…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…This effect was illustrated in previous work by Paxton et al (2012a), which observed that exposure of diamond cathodes to a low-energy hydrogen plasma prior to testing resulted in drastically enhanced thermionic emission current relative to as-grown diamond films by four orders of magnitude. Thermionic emission can be described by the Richardson equation seen in Eq.…”
mentioning
confidence: 67%
“…The temperature control loop was used to increase the temperature in roughly 5° increments up to ~900°C. Each temperature was maintained for 30 s and the emission current was constantly monitored using the same technique as previously reported (Paxton et al, 2012a). These isobaric tests were intended to determine if the presence of hydrogen would increase the emission current of diamond thermionic emitters and/or raise their operational temperature ceiling.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations